Chia seeds oil enriched with phytosterols and mucilage as a cardioprotective dietary supplement towards inflammation, oxidative stress, and dyslipidemia - Doha Mohamed; Shaimaa Mohammed; Ibrahim Hamed (Shahrekord University of Medical Sciences, 2022)
Introduction: Non-communicable diseases are a cluster of metabolic diseases, which include type-2 diabetes, cancer, and cardiovascular diseases (CVDs). The aim of the current research was to incorporate dietary fibers (mucilage) and phytosterol for enriching chia seeds oil for producing new dietary supplements for cardio-protection from oxidative stress, inflammation, and dyslipidemia. Methods: Fatty acids profile, phytosterols, and phenolic compounds content of the prepared dietary supplement were assessed. The cardioprotective potency of the dietary supplement was evaluated in rats fed on a high-fat diet for a month. Biochemical parameters related to inflammation, oxidative stress, lipid profile, cardiac enzymes, and kidney function were determined in all rats. Results: The results revealed that dietary supplement was rich in omega-3 fatty acids. Beta-sitosterol and campesterol were the major phytosterols in chia seeds oil dietary supplement. Phenolic compounds were present by 25.9 ± 1.202 mg gallic acid equivalent (GAE)/g dietary supplements. Rats fed on the high-fat diet showed significant elevation (P < 0.05) in inflammatory markers, oxidative stress, dyslipidemia, and cardiac enzymes in association with the elevation of kidney function compared with normal rats. Administration of both doses of dietary supplement significantly (P < 0.05) improved all the studied biochemical parameters. The high dose of the dietary supplement was promising in the reduction of inflammatory markers, oxidative stress, and improved dyslipidemia in accordance with the reduction of all cardiac enzymes and kidney function. Conclusion: Dietary supplements investigated in the current research showed cardioprotective potency through its anti-inflammatory and dyslipidemic activities, which may be attributed to the presence of phenolic compounds, omega-3 fatty acids, phytosterols, and soluble dietary fibers.